2022
DOI: 10.1038/s41598-022-07880-3
|View full text |Cite
|
Sign up to set email alerts
|

Low prevalence of spectacle use in the Hungarian Roma population indicates unmet health needs

Abstract: The Roma population is the largest transnational ethnic minority group in Europe, often facing socioeconomic inequalities and various health problems. In the present study, we investigated visual acuity and its influencing factors along with spectacle use of the Roma population in comparison with the general population in Hungary. A cross-sectional survey was carried out including 832 participants aged 20–64 years. We recorded the uncorrected visual acuity along with anthropometric, demographic, socioeconomic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
3
1
Order By: Relevance
“…To evaluate the observed proportions, the prevalence of using glasses or consulting an ophthalmologist was computed for other age groups. A former Hungarian survey reported a 24.0% prevalence for the 20–64-year age group [ 32 ], which was lower, while another survey published 84.3% for the 50+-year age group [ 31 ], which was higher than the corresponding values observed in our investigation (36.9% and 59.8%, respectively).…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…To evaluate the observed proportions, the prevalence of using glasses or consulting an ophthalmologist was computed for other age groups. A former Hungarian survey reported a 24.0% prevalence for the 20–64-year age group [ 32 ], which was lower, while another survey published 84.3% for the 50+-year age group [ 31 ], which was higher than the corresponding values observed in our investigation (36.9% and 59.8%, respectively).…”
Section: Discussioncontrasting
confidence: 96%
“…The prevalence of less than 0.5 visual acuity was 8.8% among 20- to 64-year-old Hungarian adults in a regional survey. The frequency of wearing glasses among participants with a visual acuity of <0.5 was 77.1% but was much less (14.3%) among participants from the ethnic minority (Roma) population, which demonstrated the presence of a huge social inequality in Hungarian eye care [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Limited information is available on the eye care of Roma children in Eastern Europe. A study of adults in Hungary published in 2022 found that in groups with visual acuity below 0.5 in both eyes, the percentage of people wearing eyeglasses was significantly lower in Roma compared to non-Roma (14.3 vs. 77.1%, p < 0.001) ( 31 ).…”
Section: Introductionmentioning
confidence: 99%
“…The Roma population in Central and Eastern Europe faces numerous challenges when it comes to accessing healthcare, resulting in a higher likelihood of unmet health needs compared to their non-Roma counterparts ( 13 , 14 ). Multiple studies have identified various barriers, including poverty, lower education levels, limited health literacy, administrative obstacles related to displacement and lack of identification documents ( 15 , 16 ).…”
Section: Introductionmentioning
confidence: 99%